EP-100 Skin Graft Versus Local Flaps in Management of Post-Burn Elbow Contracture. (9th August 2022) - Noureldin, Khaled; Issa, Mohamed; Badawi, Marwa; Darwish, Mariam; Makram, Mahmoud; Abdelazizi, Ayyat
Abstract: Introduction: Contracture is a pathological scar tissue resulting from local skin tissue damage, secondary to different local factors. It can restrict joint mobility, resulting in deformity and disability. This study aimed to investigate the outcomes of skin grafts compared to local flaps to reconstruct post-burn elbow contractures. These parameters included regaining function, range of movement, recurrence, and local complications. Methodology: A retrospective study reviewed twenty-one patients for elbow reconstruction over 12 months. Only patients with post-burn elbow contracture were included. Other causes, including previous corrective surgery, any resultant elbow stiffness, and patients who opted out of postoperative physiotherapy, were excluded. Subdivision was according to the method of coverage into three groups: graft alone(G1), local flap(G2), or combined approach(G3). Results: Females were three times at higher risk to suffer a burn injury, while almost half of the cases were children. Scald injury represented 81% of burn causes. G1, 2, 3 were used in 47.6%, 42.9% and 9.5% of cases retrospectively. Overall rate of infection was 28.5%. 100% graft taken was recorded in 81.8% of cases; however, flap take was in 90%. After 12 months of follow-up, re-contracture was 60% and 22.8% in G1 and G2; however, the satisfaction rate was 70% and 100% in both groups retrospectively. The overall satisfaction was 85.7% in all groups. Conclusion: Grafts and local flaps are reasonable options for post contracture release; however, flaps are superior. Coverage selection depends on the lost tissue area and exposure of underlying deep structures. Physiotherapy and patient satisfaction are crucial in the outcomes.